2009
DOI: 10.1093/alcalc/agp048
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Ethanol Intake and Sensitivity to Aversive Effects during Adolescence and Adulthood

Abstract: Aims: The present experiments examined sex differences in ethanol intake and in the influence of a social context on aversive properties of ethanol in adolescent and adult Sprague-Dawley rats. Methods: Experiment 1 examined ethanol intake, with animals receiving daily 2-h access to ethanol and water for 8 days. Experiment 2 assessed the aversive effects of ethanol using a conditioned taste aversion (CTA) paradigm, with animals placed either alone or with a same-sex, same-age peer during the ethanol intoxicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

41
177
5
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(231 citation statements)
references
References 44 publications
41
177
5
3
Order By: Relevance
“…This pattern of sex differences in ethanol drinking is consistent with studies reporting that isolation-housed female mice and rats produced elevated ethanol intake relative to isolation-housed male mice and rats [31,32,33,34,35,36]. The present results add to a growing body of literature indicating that these sex differences are not specific to drinking ethanol in isolation [14,15]; see also [31].…”
Section: Sex Differences In Ethanol Intakesupporting
confidence: 91%
“…This pattern of sex differences in ethanol drinking is consistent with studies reporting that isolation-housed female mice and rats produced elevated ethanol intake relative to isolation-housed male mice and rats [31,32,33,34,35,36]. The present results add to a growing body of literature indicating that these sex differences are not specific to drinking ethanol in isolation [14,15]; see also [31].…”
Section: Sex Differences In Ethanol Intakesupporting
confidence: 91%
“…This finding is consistent with previous studies showing different rewarding effects of ethanol in pubertal than juvenile or adult rats (Philpot et al 2003) and higher beer intake and binge-like drinking patterns during puberty (Hargreaves et al 2009). Additionally, adolescent rats are less sensitive to ethanol's aversive properties than adults, measured by conditioned taste aversion (Vetter-O'Hagen et al 2009). Our finding of enhanced ethanol intake in non-treated pubertal animals, and also the increased stimulatory effects of WIN on pubertal ethanol intake, might be related to some extent to the higher activity of the ECB system at puberty onset (for review see Schneider, 2008) and the higher CB 1 receptor expression observed in the present study.…”
Section: Initial Ethanol Intakementioning
confidence: 99%
“…29, nº 3 (octubre) Vetter-O´Hagen et al (2009), examinaron y ampliaron datos en relación con esta cuestión, utilizando un modelo de acceso limitado (2 h) a etanol. Sus resultados indicaron que el consumo de etanol varía, tanto en función del sexo como de la edad, aunque las diferencias sexuales que emergen en cada edad son opuestas.…”
Section: Diferencias Sexuales Y Evolutivas En Los Efectos Motivacionaunclassified
“…De hecho, la mayor parte de los estudios, realizados tanto con humanos (revisado en Song et al, 2007), como con animales (ver Anderson, Varinskaya y Spear, 2010;Doremus et al, 2005;Garcia-Burgos et al, 2009;Song et al, 2007;Vetter-O´Hagen et al, 2009), indican que los individuos adolescentes consumen mayores cantidades de alcohol que los adultos, probablemente debido a diferencias en los niveles hormonales y de neuroadaptación.…”
Section: Diferencias Sexuales Y Evolutivas En Los Efectos Motivacionaunclassified
See 1 more Smart Citation